Risk Factors Related to Pneumonia in Toddlers in the Jeuram Health Center Work Area, Nagan Raya Aceh Regency - Amiruddin; Irwansyah; Irmansyah; Burhanuddin Syam; Evi Dewi Yani; Ismail (HM Publisher, 2022)
Background: Pneumonia has several risk factors, including low exclusive breastfeeding for infants, immunization status, smoking parents, and mother's level of knowledge related to pneumonia. This study aims to analyze the relationship between risk factors and pneumonia in toddlers in the work area of ​​the Jeuram Health Center, Seunagan District, Nagan Raya Regency. Methods: This research is an observational study with a cross-sectional design. The participants in this study were all mothers with toddlers in the working area of ​​the Jeuram Health Center, with a total sample of 99 mothers. The sampling technique used was total sampling. Data analysis using SPSS. Results: Based on the results of statistical tests, it was concluded that the factors related to the incidence of pneumonia in toddlers in the working area of ​​the Jeuram Health Center, Nagan Raya Regency, namely knowledge (p-value 0.017), immunization status (p-value 0.041), exposure to cigarette smoke (p-value 0.033). Conclusion: Knowledge, immunization status, and exposure to cigarette smoke are associated with the incidence of pneumonia in toddlers.